Rancang Bangun Sistem Informasi Manajemen Organisasi Kemahasiswaan Berbasis Web di UNISNU Jepara - Pratama, Andrian Dico; Azizah, Noor; Sabilla, Alzena Dona (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
In today's digital era, Management Information Systems are becoming increasingly important for organizations and businesses. Management Information Systems can help organizations remain competitive and thrive in an increasingly complex and dynamic era. However, in student organizations within Unisnu Jepara, the management process is still carried out with manual practices and using paper media. Where writing on paper media requires a lot of time and energy, moreover the need for information in the organization is certainly abundant. Not to mention the risk of material misuse and loss of data in the future if not managed properly and correctly. The method used by researchers in this study is the Waterfall method which has 5 stages starting from Requirement Analysis, System and Software Design, Implementation and Unit Testing, System Testing and Integration, and Operation and Maintenance. The result of this research is the creation of an organizational management information system at Unisnu Jepara which is expected to help improve efficiency in the operational and management processes of student organizations at the Islamic University of Nahdlatul Ulama Jepara.